Keefektifan Pembelajaran Berbantuan Alat Peraga Perpindahan Kalor Secara Konduksi, Konveksi, dan Radiasi untuk Mendukung Pemahaman Konsep Mahasiswa - Etik Irawati; Wawan Kurniawan; Choirul Huda (Faculty of Science and Education, UIN Walisongo Semarang, 2019)
Research has been successfully carried out about the effectiveness of learning assisted by props of heat transfer by conduction, convection, and radiation to support the understanding of student concepts. This study uses a quasi-experimental method. This research was conducted at the Universitas PGRI Semarang, S1 Department of Mathematics Education which took Fundamental Physics courses in semester 2 of the 2018/2019 academic year. The research sample was 41 students. Data collection techniques in this study were conducted using tests and questionnaires. Statistical techniques used paired sample t-test. From the research, it was found that the use of heat transfer props in effective learning to support students' conceptual understanding.